9. LEGAL RECONSTRUCTION OF ALTERNATIVES TO DETENTION (ATD) INTHE INDONESIAN IMMIGRATION DETENTION SYSTEM: INTERNATIONALAND LOCAL PERSPECTIVES - Muhammad Davel Ramadhasyena Davidsonputra; Nur Priyanto; Suroso; Anwar Hendro; Tutidikatama; Hendri Himawan; Muchammad Furqon (Staf Komunikasi dan Elektronika, TNI Angkatan Udara, 2026)
This study aims to analyze the legal framework of Alternatives to Detention (AtD)in the international immigration system and compare it with the immigration detention systemin Indonesia. Furthermore, this study also aims to formulate a legal reconstruction model forAtD that is suitable for application in the Indonesian immigration detention system, taking intoaccount the juridical, institutional, and socio-cultural aspects. The research method used isnormative-doctrinal legal research, with a legislative, conceptual, comparative, and case-basedapproach. Data were collected through documentation studies, interviews with relevantstakeholders, and case studies of the implementation of AtD in other countries such asAustralia, Belgium, Canada, and Thailand. The data analysis techniques used are qualitativeand comparative analysis to evaluate Indonesia's immigration detention policy and theopportunities and challenges of AtD implementation. The results of the study indicate thatalthough Indonesia has adopted several international principles related to human rights, theapplication of AtD in the Indonesian immigration system is still very limited. This studyrecommends regulatory changes, institutional strengthening, and public education to createacceptance for refugees and immigrants. A more comprehensive implementation of AtD canimprove the immigration system to be more humane, effective, and in line with internationalstandards.